Djibouti : 2015 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This 2015 Article IV Consultation highlights that Djibouti's economic growth, driven by large investment projects, continued its rapid pace in 2014. Aggregate investment reached 44 percent of GDP in 2014 and is expected to peak at 57 percent in 2015-16. GDP growth is expected to rise from 6 percent in 2014 to about 6.5 percent in 2015-16 and to 7 percent in 2017-19. Inflation is projected at 3 percent in 2015 and about 3.5 percent in 2016-18 as a large amount of infrastructure spending increases the demand for housing and services. Central bank gross foreign assets are projected to remain strong, permitting full currency board coverage over the period 2015-20.